Ultrasonic Nebulisation Extraction: Extraction Column Coupled with Liquid Phase Microextraction for Analysis of the Volatile Organic Compounds in Foeniculum vulgare Mill. as a Model. Issue 4 (25th October 2012) - Yu, Cui; Yang, Jinjuan; Wang, Yeqiang; Wei, Hongmin; Zhang, Hanqi; Shi, Yuhua
ABSTRACT: Introduction: As the concentrations of the volatile organic compounds are always low and their matrix is complex, it is necessary to pre‐concentrate the volatile organic compounds before analysis. Ultrasonic nebulisation extraction with a self‐made extraction column coupled with liquid phase microextraction is developed for the extraction of active constituents from spices. Objective: To develop an environmentally compatible extraction technique for the preparation and analysis of the volatile organic compounds from spices. Method: The sample is placed into the nebulisation vessel of a nebulisation humidifier and a purging gas is blown through the vessel continuously. When the nebuliser is switched on, a ultrasonic fountain is formed by ultrasonic vibration and the target analytes are transferred from the sample solution to the vapour phase and then concentrated on the extraction solvent in the extraction column. After extraction for 3 min and allowed to stand upright for 5 min, the extract is analysed by GC and GC–MS. Different methods of comparison can then be carried out. Results: Optimum conditions were found to be: 30 μL of n ‐tetradecane as the extraction solvent, a flow rate for the purging gas of 40 mL/min, a purging time of 3 min and a standing time was 5 min. The contents of constituents in the extract obtained by the proposed method were close to those obtained by hydrodistillation (HD). Moreover, the proposed method achieves higher enrichment efficiency. Conclusion: A method was developed for the extraction of volatile organic compounds from spices. The study has shown that it is a fast and environmentally sustainable technique. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : The ultrasonic nebulization extraction with a self‐made extraction column coupled with liquid phase microextraction is developed for the extraction of active constituents from spices. The analytes were nebulized by ultrasonic vibration and transferred into the vapor phase and then concentrated in the extraction column followed by the purging gas. The contents of constituents in the extract obtained by the proposed method were closer to those obtained by hydro‐distillation (HD). Moreover, it achieves higher enrichment efficiency.